Anthropogenic materials used by birds to nest in an urban landscape of Costa Rica - Esquivel, Carolina (2020)
Introduction: Urbanization has affectedthe materials available for bird nesting, including anthropogenic materials that may be dangerous to the birds. Objective:To quantifythe materials used byseveral bird species in an urbanized environment. Methods: We evaluated the composition of 20 nests in the campus of Universidad Nacional, Costa Rica. Results: 53% of nests contained anthropogenic waste,classified in 13 types;the most common were wool, strings and thread. The species with the highest percentage of anthropogenic nest weight was Campylorhynchus rufinucha. Conclusion: There is awidespread use of anthropogenic materials to nest in these urban Costa Rican birds.